2016
DOI: 10.1128/jb.00030-16
|View full text |Cite
|
Sign up to set email alerts
|

The UbiI (VisC) Aerobic Ubiquinone Synthase Is Required for Expression of Type 1 Pili, Biofilm Formation, and Pathogenesis in Uropathogenic Escherichia coli

Abstract: Uropathogenic Escherichia coli (UPEC), which causes the majority of urinary tract infections (UTI), uses pilus-mediated adherence to initiate biofilm formation in the urinary tract. Oxygen gradients within E. coli biofilms regulate expression and localization of adhesive type 1 pili. A transposon mutant screen for strains defective in biofilm formation identified the ubiI (formerly visC) aerobic ubiquinone synthase gene as critical for UPEC biofilm formation. In this study, we characterized a nonpolar ubiI del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 81 publications
1
26
0
Order By: Relevance
“…The isolates with moderate to strong biofilm formation ability showed higher type 1 fimbria expression level compared to the bacteria with poor biofilm formation potential. This finding indicates that phenotypic expression of the type 1 fimbria is an important determinant in biofilm formation by UPEC (13,20). Soto et al (13) reported that expression of the type 1 fimbria is independently associated with biofilm formation, which was in accordance with our data.…”
Section: Discussionsupporting
confidence: 92%
“…The isolates with moderate to strong biofilm formation ability showed higher type 1 fimbria expression level compared to the bacteria with poor biofilm formation potential. This finding indicates that phenotypic expression of the type 1 fimbria is an important determinant in biofilm formation by UPEC (13,20). Soto et al (13) reported that expression of the type 1 fimbria is independently associated with biofilm formation, which was in accordance with our data.…”
Section: Discussionsupporting
confidence: 92%
“…S20). VisC is involved in energy production for the cell and a knockout reduced membrane potential in uropathogenic E. coli (34). The visC results suggested our measurements were sensitive enough to find variants that alter calcium flux, but the 175 genes tested are unlikely to relay mechanosensation or the voltage-gated calcium current.…”
Section: No Individual Mechanosensitive Channel Controls Mechanicallymentioning
confidence: 92%
“…On the following day, protein A/G plus agarose beads were added to the negative IgG control samples and incubated for 1 hour at 4°C with rotation. Afterwards, the beads or resin samples were pelleted, washed six times, and boiled in acidified Laemelli lysis buffer as previously described for adherence proteins(88). After boiling, samples were neutralized with basic Laemelli lysis buffer.…”
Section: Methodsmentioning
confidence: 99%